Avian influenza surveillance: on the usability of FTA - Kraus, Robert H S; van Hooft, Pim; Waldenström, Jonas; Latorre-Margalef, Neus; Ydenberg, Ronald C; Prins, Herbert H T (Wildfowl, 2013)
Many zoonotic diseases have birds as their natural hosts. Waterfowl are the natural hosts of avian influenza viruses (AIVs) and most avian influenza infections of wild birds appear mild, with infected inviduals displaying no or few symptoms. It is clear that the epidemiology of avian influenza cannot be fully understood without taking the ecology of its hosts into account. However, large scale studies and surveillance are still hampered by issues about preservation, transport and storage of AIVs, including bio-safety regulations and maintaining samples. This complicates the possibilities of the many small projects across the world if they are not done within the framework of one of the few big projects. Here, evidence is provided of the potential for using Whatman FTAÂ® cards as a new preservation method to solve the above mentioned issues. Its efficiency is comparable to that of a standard method in virology, and saves time and money. In both large scale AIV sampling and small scale independent projects this method might be the means by which the field of the AIV ecology will be lifted beyond the constraints of difficult and expensive sampling, storage and laboratory facilities.